Characterization of the complete mitochondrial genome of Cynoglossus nanhaiensis (Pleuronectiformes: Cynoglossidae) - SiLin Tian; Chen Wang; Yunrong Yan; Xiao Chen (Mitochondrial DNA. Part B. Resources, 2020)
In this study, the complete mitochondrial genome of Cynoglossus nanhaiensis was determined. The total length of the mitochondrial genome is 17,130 bp, including 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and two noncoding regions. The gene rearrangement of tRNAGln gene and control region (CR) were detected, forming a unique gene order of CR-Ile-Gln-Met. Maximum-likelihood and Bayesian inference method are used to perform the phylogenetic analysis, and the result reveals a close relationship between C. nanhaiensis and Cynoglossus itinus.